BIOLOGY OF Cerotoma facialisl COMMON BEANE PEST, Phaseolus vulgaris L. - GONZÁLEZ, RANULFO; CARDONA, CÉSAR (Revista Colombiana de Entomología, 1979)
The biology of Cerotoma facialis (Erickson), a chrysomelid commonly occurring in bean crops in Colombia, was studied under laboratory conditions (27°C, 80% RH). All developmental stages of the insect were measured and described. The morphological characteristics of its immature stages are similar to those of other Galerucinae species. Morphological differences are described which facilitate sex differentiation of adults, as well as phenological variations in adult specimens. Eggs have a mean duration of 6,4 days, larval stages varied from 9 to 12 days (first instar, 3-4 days, mean 3,5 days; second instar, 2-3 days, mean 2,6 days; and third instar, 4-5 days; the prepupal stage had a mean duration of 2,9 days, and the pupal stage, 6,4 days. The sex ratio was 1:1. The preoviposition period varied between 5 and 7 days and the maximum number of eggs laid per female was 532. Females can live up to 75 days under natural conditions. The complete biological cycle of C. facialis from egg to adult emergence, varíes from 22 to 33 days.